Techniques for Obtaining High-quality Recordings in Electrocochleography - Michael J. Simpson; Skyler G. Jennings; Robert H. Margolis (Frontiers in Systems Neuroscience, 2020)
There are several technical challenges to obtaining high-quality recordings of cochlear potentials in human electrocochleography (ECochG). These challenges include electrical artifacts from devices such as acoustic transducers, biological artifacts from excessive myogenic and electroencephalographic potentials, and issues associated with the placement of a tympanic membrane (TM) electrode on the eardrum. This article presents approaches for dealing with these challenges for ECochG measurement using a TM electrode. Emphasis is placed on eliminating stimulus artifact, optimizing the placement of the electrode, and comparing a custom-made electrode with a commercially-available electrode. This comparison revealed that the custom-made electrode results in greater subject comfort, superior ease of placing the electrode on the eardrum, and larger compound action potential (CAP) amplitudes.